Deskripsi Proses Pembelajaran IPAS Dengan Memanfaatkan Teknologi Informasi dan Komunikasi di Sekolah Dasar Negeri 28 Pontianak Kota - Susilawati Susilawati; Hery Kresnadi; Bistari Bistari (Departement of Mathematics Education, 2023)
This research was conducted to describe the science learning process in utilizing Information and Communication Technology. This study used descriptive qualitative method. The sample is 2 teachers in class IV SDN 28 Pontianak City. Data collection techniques used are observation and interviews. The research data analysis technique uses the Miles and Huberman model. The results showed the implementation of science learning using ICT, in the core learning activities the teacher used ICT more often, in the preliminary and closing activities of learning only occasionally. Intensity Utilization of teachers looks enthusiastic and the number of applications using power point only. Teachers have obstacles in utilizing ICT, such as a lack of facilities and infrastructure, for example ICT devices that are lacking to operate properly, lack of technicians, lack of time in teaching due to too long to install ICT devices and lack of funding to facilitate computer labs . The solution is the school must improve infrastructure better, provide ICT facilities in each class and provide regular teacher training. Can be concluded that the implementation of science learning by utilizing ICT, teachers are more dominant in using it in the core learning activities.